2018
DOI: 10.1007/978-3-319-72362-4_14
|View full text |Cite
|
Sign up to set email alerts
|

Waste Heat Recovery from Aluminum Production

Abstract: Around half of the energy consumed in aluminum production is lost as waste heat. Approximately 30-45% of the total waste heat is carried away by the exhaust gas from the smelter which is the most easily accessible waste heat stream. Alcoa Fjardaal in east Iceland produces 350 000 tons annually, emitting the 110 °C exhaust gas with 88.1 MW of heat. This work concentrates on creating and comparing models of low-temperature energy utilization from the aluminum production. Three scenarios, including organic Rankin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…For exhaust gas temperatures between 200 and 300 • C, the best option found was an ORC with R141b as working fluid. As far as aluminum production plants are concerned, recently, Yu et al (2018) assessed the performance of heat recovery ORCs for an aluminum production plant located in Iceland wasting about 88 MW of thermal power from the smelter exhaust gases.…”
Section: Introductionmentioning
confidence: 99%
“…For exhaust gas temperatures between 200 and 300 • C, the best option found was an ORC with R141b as working fluid. As far as aluminum production plants are concerned, recently, Yu et al (2018) assessed the performance of heat recovery ORCs for an aluminum production plant located in Iceland wasting about 88 MW of thermal power from the smelter exhaust gases.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of devices in each candidate solution is determined through physical analysis to maximize WHR utilization. A comparison is then performed among these solutions to identify the optimal candidate (Hassan, 2015;Pantaleo et al, 2018;Yu et al, 2018). For instance, Yu et al (Yu et al, 2018) defined three scenarios for WHR utilization from exhaust gas in the aluminum industry and compared the exergy efficiency and energy output power of these schemes.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison is then performed among these solutions to identify the optimal candidate (Hassan, 2015;Pantaleo et al, 2018;Yu et al, 2018). For instance, Yu et al (Yu et al, 2018) defined three scenarios for WHR utilization from exhaust gas in the aluminum industry and compared the exergy efficiency and energy output power of these schemes. Their findings demonstrated that two of these scenarios adequately met the local basic space-heating load.…”
Section: Introductionmentioning
confidence: 99%